Influence of geographic origin, sex, and HIV transmission group on the outcome of first-line combined antiretroviral therapy in France. (10th September 2016) - de Monteynard, Laure-Amélie; Matheron, Sophie; Gilquin, Jacques; Pavie, Juliette; de Truchis, Pierre; Grabar, Sophie; Launay, Odile; Meynard, Jean-Luc; Khuong-Josses, Marie-Aude; Rey, David; Simon, Anne; Mahamat, Aba; et al.
Abstract : Background: More data are needed on the influence of geographic origin, sex, and the HIV transmission group on biological and clinical outcomes after first-line combined antiretroviral therapy (cART) initiation. Methods: We studied antiretroviral-naive HIV-1-infected adults enrolled in the French Hospital Database on HIV cohort in France and who started cART between 2006 and 2011. The censoring date of the study was 31 December 2012. According to geographic origin [French natives (FRA) or sub-Saharan Africa/non-French West Indies (SSA/NFW)], sex, and HIV transmission group, we assessed 2-year Kaplan–Meier probabilities and adjusted hazard ratios (aHRs) for plasma viral load undetectability and CD4 + cell recovery, and 5-year cumulative incidences and aHRs for negative clinical outcomes (AIDS-defining event, serious non-AIDS events, or death). Results: Of 9746 eligible individuals, 7297 (74.9%) were FRA and 2449 (25.1%) were sub-Saharan Africa/non-French West Indies migrants. More migrants (38.1%) than nonmigrants (27.5%) started cART with a CD4 + cell count less than 200/μl ( P  < 0.0001). By comparison with FRA MSM, nonhomosexual men, whatever their geographic origin, had lower aHRs for viral undetectability; all patient groups, particularly migrants, had lower aHRs for CD4 + cell recovery than FRA MSM; aHRs for negative clinical outcome (360 new AIDS-defining events, 1376 serious non-AIDS events, 38 deaths) were also higher in nonhomosexual men, regardless of geographic origin. Preexisting AIDS status, a lower CD4 + cell count and older age at cART initiation had the biggest impact on changes between the crude and aHRs of clinical outcomes. Conclusion: Compared with FRA MSM, all migrants had a lower likelihood of CD4 + cell recovery, and nonhomosexual men had a higher likelihood of negative virological and clinical outcomes.